A new PAPR reduction technique for OFDM-WLAN in 802.11a systems - Pradabpet, C.; Eupree, K.; Chivapreecha, S.; Dejhan, K. (My University, 2008)
In this paper, we proposed a new PAPR reduction technique using selective mapping (SLM) cascade with adaptive peak power reduction (APPR) methods. This technique is used in a system based on Orthogonal Frequency Division Multiplexing (OFDM). OFDM has many orthogonally modulated sub-carriers which unexpectedly produce high peak to average power ratio (PAPR). The high PAPR will occasionally reach the amplifier saturation region and therefore result in signal distortion, which causes bit error rate (BER) degradation. The proposed method, a sequence of input data is rearranged by SLM for the reduction of PAPR and then fed into the APPR process in the proposed system. The APPR method controls the peak levels of the modulation signal by an adaptive algorithm. It reduces modulation signals over a predefined range. The parameter for simulation used standard WLAN in IEEE 802.11a system. In simulation results, the proposed method shows the improvement on PAPR, power spectrum density(PSD) and high performance BER compared with conventional APPR. © 2008 IEEE.